Surface Expression of Toll-Like Receptor 9 Is Upregulated on Intestinal Epithelial Cells in Response to Pathogenic Bacterial DNA - Ewaschuk, Julia B. (American Society for Microbiology, 2007)
Colonic epithelial cells are constantly exposed to high levels of bacterial DNA in the intestinal lumen and must recognize and respond appropriately to pathogens, while they maintain a tolerance to nonpathogenic commensal bacterial strains. Bacterial DNA is recognized by Toll-like receptor 9 (TLR9). The aim of this study was to investigate TLR9 expression and localization in colonic epithelial cells under basal conditions and in response to bacterial DNA. HT-29 cells were exposed to DNA from various strains of commensal and pathogenic microbes. TLR9 mRNA expression was determined by real-time reverse transcription-PCR, and interleukin-8 (IL-8) secretion was measured by an enzyme-linked immunosorbent assay. Localization of TLR9 was determined by flow cytometry in HT-29 cells and by immunofluorescence in HT-29 cells and mouse colonic tissue. Immunofluorescence and flow cytometric analyses demonstrated that there was intracellular and surface expression of TLR9 in HT-29 cells under basal conditions. Exposure of cells to DNA from pathogenic strains of Salmonella and Escherichia coli resulted in a significant increase in TLR9 mRNA expression. Salmonella enterica serovar Dublin DNA increased surface TLR9 protein and IL-8 secretion. There was no change in mRNA levels or localization of TLR9 in response to Bifidobacterium breve. Chloroquine did not block IL-8 secretion in response to S. enterica serovar Dublin DNA. TLR9 was expressed on the colonic apical surface in wild-type mice but not in germfree mice. These results demonstrate that intestinal epithelial cells recognize pathogenic bacterial DNA and respond by increasing surface localization and expression of TLR9, suggesting that the epithelial inflammatory response to pathogenic DNA is mediated at least in part by increased TLR9 expression.